Development of HRES with Monitoring System - Mohd Farid, Muhammad Fitri Najmi; Bohari, Azuwien Aida (Progress in Engineering Application and Technology, 2024)
Development of Hybrid Renewable Energy System (HRES) with integrated system monitoring capabilities to address the growing need for sustainable and efficient energy solutions. This innovative system harnesses solar, hydro, and wind energy by developing a small-scale prototype that leverages the strengths of each energy source. The methodology involves the design and implementation of a compact, multi-source energy generation unit, utilizing photovoltaic panels to capture solar energy, a micro-hydro generator to harness hydro energy, and wind turbines to exploit wind energy. Detailed design considerations were made to ensure optimal energy conversion and storage. The developed prototype is equipped with IoT features for real-time data monitoring, allowing for continuous performance tracking and system diagnostics. This real-time monitoring capability not only ensures the system’s operational efficiency but also provides valuable data for future improvements and scalability. The prototype shows a practical solution for small-scale power generation, emphasizing the importance of integrating multiple renewable energy sources with advanced monitoring technologies to achieve sustainable and efficient energy systems.